Short- and Long-Lived Autoantibody-Secreting Cells in Autoimmune Neurological Disorders - Zografou, C.; Vakrakou, A. G.; Stathopoulos, P. (Frontiers in Immunology, 2021)
As B cells differentiate into antibody-secreting cells (ASCs), short-lived plasmablasts (SLPBs) are produced by a primary extrafollicular response, followed by the generation of memory B cells and long-lived plasma cells (LLPCs) in germinal centers (GCs). Generation of IgG4 antibodies is T helper type 2 (Th2) and IL-4, -13, and -10-driven and can occur parallel to IgE, in response to chronic stimulation by allergens and helminths. Although IgG4 antibodies are non-crosslinking and have limited ability to mobilize complement and cellular cytotoxicity, when self-tolerance is lost, they can disrupt ligand-receptor binding and cause a wide range of autoimmune disorders including neurological autoimmunity. In myasthenia gravis with predominantly IgG4 autoantibodies against muscle-specific kinase (MuSK), it has been observed that one-time CD20+ B cell depletion with rituximab commonly leads to long-term remission and a marked reduction in autoantibody titer, pointing to a short-lived nature of autoantibody-secreting cells. This is also observed in other predominantly IgG4 autoantibody-mediated neurological disorders, such as chronic inflammatory demyelinating polyneuropathy and autoimmune encephalitis with autoantibodies against the Ranvier paranode and juxtaparanode, respectively, and extends beyond neurological autoimmunity as well. Although IgG1 autoantibody-mediated neurological disorders can also respond well to rituximab induction therapy in combination with an autoantibody titer drop, remission tends to be less long-lasting and cases where titers are refractory tend to occur more often than in IgG4 autoimmunity. Moreover, presence of GC-like structures in the thymus of myasthenic patients with predominantly IgG1 autoantibodies against the acetylcholine receptor and in ovarian teratomas of autoimmune encephalitis patients with predominantly IgG1 autoantibodies against the N‐methyl‐d‐aspartate receptor (NMDAR) confers increased the ability to generate LLPCs. Here, we review available information on the short-and long-lived nature of ASCs in IgG1 and IgG4 autoantibody-mediated neurological disorders and highlight common mechanisms as well as differences, all of which can inform therapeutic strategies and personalized medical approaches.